Exploring the Language of Consumption - Filippo Pietrini (Œconomia)
This article applies computational linguistics to 112 articles about consumption, published in the American Economic Review, Econometrica, and the Journal of Economic Issues. Following Lee et al. (2010) distinction between “mainstream” and “heterodox” journals, our analysis compares the linguistic content of the articles on consumption published by American Economic Review/Econometrica, with that of articles from the Journal of Economic Issues. Findings reveal that different theoretical approaches use substantially different languages. Articles published by the Journal of Economic Issues use a more extensive vocabulary and a wider range of collocations, focusing on the social dimension of consumption and interdependent preferences. They also engage more in theoretical discussions and reference various scientific fields. In contrast, articles in American Economic Review/Econometrica lean towards technical language, addressing the intertemporal aspect of preferences and individual facets of consumption, and only refer to other research in economics. These results show that the set of computational linguistics’ methods used in the article can be effective in identifying theoretical and methodological divides across different streams of literature.